REKONSTRUKSI EVALUASI PEMBELAJARAN DALAM PERSPEKTIF PENDIDIKAN ISLAM - Abdul Aziz Mustamin; Idi Warsah (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2022)
Islamic education aims to develop the natural potential that exists in humans to become human beings. So that all components in education must be in accordance with the goals of Islamic education. To find out whether or not these goals are achieved, an evaluation is needed. This study uses a literature study by examining several books and thoughts of figures, researchers will discuss more deeply about the evaluation of Islamic education both in terms of epistemology, terminology, axiology, and ontology. Evaluation can be interpreted as an effort made to determine the level of success and weakness of an Islamic education process, which includes all the components in it to achieve the goals that have been set. In the implementation process, the evaluation must apply several principles, techniques and procedures that must be followed for the good results to be obtained.